Seed Germination Indicates Adaptive Transgenerational Plasticity in a Submerged Macrophyte - Su, Hong; Zhu, Tianshun; Bai, Xiaohu; Ni, Leyi; Xie, Ping; Zhang, Xiaolin (Frontiers in Plant Science, 2018)
Adaptive transgenerational plasticity is an important evolutionary strategy in plants. We investigated the resource allocation strategy in sexual reproduction and performed an in-situ seed germination experiment of Potamogeton maackianus to reveal their responses to different water depths. Then we discussed the biased adaptability to maternal habitat in this species. We found a positive correlation between sexual and asexual reproductions in water depths from 1.0 to 3.0 m, such correlation didn’t occur in 4.0 m water depth. These results indicate the trade-off between sexual and asexual reproduction should only be expected in stressful habitat, where resource acquisition is limited. For trade-off between quantity and quality of sexual units in different water depths, P. maackianus tends to produce more but lower quality sexual reproductive units in shallow water, and fewer but higher quality sexual units are found in deep water. The total germination percentage of seeds of P. maackianus was relatively poor, less than 46.65% in all of the treatments. The maximum germination percentage of seeds from 1.0, 2.0, 3.0 and 4.0 m water depths are 14.4%, 17.75%, 25.51% and 46.65% respectively. Seeds with higher germination percentage were from deeper water depth. The most interesting result was that the maximum final germination percentage occurred only when treatment water depth was the same as collection water depth. Our result showed that the variations in germination characters of the studied species appear to be based partly on the effects of maternal environmental factors. Our findings proved the adaptive transgenerational plasticity in P. maackianus, which will play an important role in evolutionary response to selection of water depths.